Edukasi Terapi Komplementer Bekam dalam Pencegahan Penyakit Tidak Menular Hypertensi pada Masyarakat Nelayan Desa Pekaroa, Kecamatan Sawa - Hadi, Indriono; Rosyanti, Lilin; Purnama, Dwi; Syahrianti, Syahrianti; Sarita, Sultina (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Hypertension is a common non-communicable disease in the fishing population. Complementary cupping therapy can be used as one of the non-pharmacological strategies in preventing hypertension. The purpose of this community service is to improve the community's knowledge and attitude in implementing cupping therapy in preventing hypertension. The methods and approaches of community service include several stages and strategies that are effective in improving public health, namely: Preparation and Coordination; Implementation of Activities, Pre-test and Post-test; counseling and simulation of cupping therapy practice; Evaluation and Monitoring. The results, before counseling and practice, the level of knowledge of participants; sufficient 15%, lacking 85%. After counseling and practice, knowledge; good 30%, sufficient 70%, and lacking 0%. The attitudes of counseling participants after counseling and practice were strongly agree as much as 63.3%, agree as much as 31.67%, and disagree as much as 5%. It is hoped that fishing communities can use Complementary cupping therapy in improving health